The policy implementation of DKI Jakarta Provincial Government social cash assistance during COVID-19 pandemic - Muhammad Haikal; Rachma Fitriati (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2023)
Provision of social assistance in handling the impact of Covid-19 has been carried out in various countries since 2020. It also has been provided to communities which affected by Covid-19 in the DKI Jakarta Province in the form of groceries in 2020 and changed to cash in 2021, known as Bantuan Sosial Tunai (BST) or social cash transfer. In the previous studies, the implementation of the provision of social assistance in the form of groceries is considered as problematic issue in fact of the poor quality of assistance and invalid beneficiary data. This article intends to explain the implementation of policy in BST of DKI Jakarta Provincial Government during Covid-19 pandemic. Therefore, this article will uses the policy implementation framework from Mazmanian and Sabatier (1989) with three variables which are: the characteristics of the problem, the characteristics of the policy, and the environmental policy. This study uses a qualitative approach and descriptive study that aims to provide an overview of the implementation of the BST Provincial Government of DKI Jakarta. BST was given for 6 months, with total value of IDR 300,000/month/head of family. The results of the study show that the implementation has been carried out properly because it is supported by a complete set of rules (characteristics policy). Furthermore, the implementation has received support from the community, legislative branch, and the governor (environmental policy). There was a constraint that occurred in updating data and the process of distributing passbooks and ATM cards (characteristics of the problem).